Epigenetic regulation of reprogramming and pluripotency: insights from histone modifications and their implications for cancer stem cell therapies - Bae, Woori; Ra, Eun A.; Lee, Myon Hee (Frontiers in Cell and Developmental Biology, 2025)
Pluripotent stem cells (PSCs) possess the extraordinary capability to differentiate into a variety of cell types. This capability is tightly regulated by epigenetic mechanisms, particularly histone modifications. Moreover, the reprogramming of somatic or fate-committed cells into induced pluripotent stem cells (iPSCs) largely relies on these modifications, such as histone methylation and acetylation of histones. While extensive research has been conducted utilizing mouse models, the significance of histone modifications in human iPSCs is gaining increasing recognition. Recent studies underscore the importance of epigenetic regulators in both the reprogramming process and the regulation of cancer stem cells (CSCs), which are pivotal in tumor initiation and the development of treatment resistance. This review elucidates the dynamic alterations in histone modifications that impact reprogramming and emphasizes the necessity for a balance between activating and repressive marks. These epigenetic marks are influenced by enzymes such as DNA methyltransferases (DNMTs) and histone deacetylases (HDACs). Furthermore, this review explores therapeutic strategies aimed at targeting these epigenetic modifications to enhance treatment efficacy in cancer while advancing the understanding of pluripotency and reprogramming. Despite promising developments in the creation of inhibitors for histone-modifying enzymes, challenges such as selectivity and therapy resistance continue to pose significant hurdles. Therefore, future endeavors must prioritize biomarker-driven approaches and gene-editing technologies to optimize the efficacy of epigenetic therapies.